La Normatividad Coercitiva en la Discriminación del Derecho al Trabajo de las Personas con Discapacidad, en las Entidades Públicas y Privadas, Vulnera el Principio Constitucional de Igualdad - Castillo Armijos, María José (2016)
This research paper entitled " coercive regulations on discrimination the right to work of persons with disabilities in public and private entities, violates the constitutional principle of equality", set off on an analysis of the labor access of people with disabilities in public and private entities, jointly compliance with the laws that protect this vulnerable population groups considered by the Constitution of the Republic of Ecuador on equal opportunities. This study was of great importance to know the reality in which people living with disabilities in the workplace; regarding changes in what and how strategies have been made lately in this way to benefit this vulnerable group in Ecuador. To fulfill the objectives I proceeded to make a critical, legal and doctrinal study of the employment of persons with disabilities equal opportunities to demonstrate the need for creation of coercive legal rules that guarantee the right to normed work in the Constitution. This study was aimed at public and private entities to discuss and consider whether there is compliance with the right to employment access that people with disabilities without any discrimination; and the lack of coercive measuresto establish servers that do not perform their duties fully, by the respective authorities. 5 Within this dissertation it was reviewed and analyzed existing laws that protect those persons with disabilities, analyzing certain articles of each of the legal rules ensuring the labor access of these people to a work place in public and private entities; and social interest is also the content of public strategies that we have drawn. For this, it was a great collaboration to provide the respective information that the public and private entities provided us with regard to the surveys to clarify the projected objectives and fully defend the investigation